Determination of vitamin E in margarines and edible oils using square wave anodic stripping voltammetry with a glassy carbon paste electrode - Sýs, Milan; Švecová, Blanka; Švancara, Ivan; Metelka, Radovan (My University, 2017)
A new electroanalytical method for determination of vitamin E in the form of the total content of tocopherols present in margarines and edible oils has been developed. The method is based on extraction of these biologically active compounds into silicone oil, acting as lipophilic binder of glassy carbon paste electrode, with subsequent electrochemical detection by square wave anodic stripping voltammetry (SWASV) in 0.1 M HNO3. The values of vitamin E contents were expressed as mass equivalent of alpha-tocopherol known as the most active form of this lipophilic vitamin. The linear ranges for alpha-tocopherol determination were 5 x 10(-7)-4 x 10(-5) and 5 x 10(-8)-1 x 10(-5) mol L-1 with the detection limits of 1 x 10(-7) and 3.3 x 10(-9) mol L-1 for 5 and 15 min accumulation, respectively. The results have shown that SWASV with extraction step is very sensitive method for the determination of vitamin E, being comparable to reversed-phase high performance liquid chromatography chosen as reference method.
Stanovení vitamínu E v margarínech a jedlých olejích pomocí square wave anodické rozpouštěcí voltametrie na pastové elektrodě ze skelného uhlíku
Keywords: Carbon paste electrode; square wave voltammetry; extraction; vitamin E; tocopherols; edible oils; margarines; Uhlíková pastová elektroda; square wave voltametrie; extrakce; vitamín E; tokoferoly; jedlé oleje; margaríny